(untitled) (Informatica, 2024)
The intelligence of computers is the future development direction. In today’s society, the amount of information is increasing, putting higher requirements for retrieval technology and automation. With the development and popularization of the Internet era, online shopping, study, and even work have become the norm in people’s lives. However, a large amount of data is generated on the Internet every day, and how to obtain the information people need from this data is a crucial research problem today. It can be seen that the traditional global search or image search can no longer meet the amount of information people need, so the content-based search method will inevitably become a more popular database retrieval technology. In recent years, content-based image capture has become a research center in image information removal. This article first studies image processing and capture technology. It provides a detailed overview of image segmentation technology and image segmentation models introduced in image processing, as well as three image segmentation methods. This article also introduces the basic principles and framework of the CBIR procurement system. The most important technology in the CBIR system is the analysis and description of image features and several methods commonly used to express the content of feature images. Secondly, it analyzes the image edge detection algorithm in detail and introduces the functional division and workflow of the library book automatic recognition system (ARS). It also provides all the construction environments, processes, and algorithms to perform the essential functions of the system.